Thoraco-abdominal asynchrony analysis using optoelectronic plethysmography in patients with cervical spinal cord injury - Hanayama, K.; Takefumi, S.; Akio, T.; Takashi, H.; Hiromichi, M.; Sousuke, S.; Masaki, H. (Annals of physical and rehabilitation medicine, 2018)
Patients with acute cervical spinal cord injury (CSCI) sometimes present paradoxical respiratory pattern, that is, the chest cage is displaced inward during inspiration. It is known as an example of thoraco-abdominal asynchrony which increases work of breathing. On the other hand, it is known that respiratory movement of such paralytic patients are influenced by position change. The aim of this study was to investigate thoraco-abdominal asynchrony and influence of posture on it in patients with chronic cervical spinal cord injury using optoelectronic plethysmography. Five patients with chronic CSCI (aged 42±14, ASIA impairment scale classified into A in all patients, neurological level C4: 2, C5: 2, C8: 1) were recruited from outpatient clinic of regional rehabilitation center. As control group, 5 age-gender matched healthy subjects were recruited. Volume change of the rib cage and the abdomen were measured with 3 dimention optoelectronic motion analysis system (VICON MX, Motion Capture Systems, Oxford, UK), using 45 reflective markers on the chest wall monitored by 6 infrared cameras. The breath which showed maximum volume change among 3 deep breaths was sampled for analysis in each patient. Measurement was done in the supine position and 30 and 60 degrees head elevation position. With obtained volume change of rib cage and abdomen, Konno Mead Diagram was drawn for each sample. Then we calculated the phase shift angle. The phase shift angle was 47±2 degrees for the patients and 9±6 degrees for healthy controls in supine position, that is, the CSCI patients group showed larger abdominal contribution. The angle tended to increase as head elevation in both groups. Patients with chronic CSCI showed larger asynchrony than healthy controls. Asynchrony tended to increase with head raising in both CSCI patients and controls.